Transformation of the Ukrainian Economy – Towards EU Integration - Baszyński, Adam (Луцьк : Вежа-Друк, 2023)
An important step towards institutional reconstruction was the introduction of the administrative-territorial reform in 2015, which aimed to increase administrative efficiency and decentralise power. However, institutional reconstruction in Ukraine is still a difficult and ambiguous process. The transformation to lead to EU accession requires further uncompromising reforms to build a demacratic rule of law with a tripartite government, a strong state and independent courts, an independent and free media, and harmonisation of the tax system, the financial sector, including the banking services market, and state economic policy. Efforts on the part of the Ukrainian authorities and civil society should create a stable, free and democratic state.
Трансформація української економіки – шлях до інтеграції в ЄС
Keywords: transformation; Ukraine; macroeconomic stabilisation; sustainable political; 338.926:339.9(4-15)